Haematopoietic depletion in vaccine-induced neonatal pancytopenia depends on both the titre and specificity of alloantibody and levels of MHC I expression. Issue 30 (9th July 2015) - Bell, Charlotte R.; MacHugh, Niall D.; Connelley, Timothy K.; Degnan, Kathryn; Morrison, W. Ivan
Highlights: MHC I-specific alloantibodies play a dominant role in Bovine Neonatal Pancytopenia. 50% of Pregsure-vaccinated cows produce MDBK-MHC I-specific alloantibodies. Pregsure-vaccinated cows produce variable titres and specificities of alloantibody. Alloantibody damage to haematopoietic cells is due to their high MHC I expression. Abstract: Bovine Neonatal Pancytopenia (BNP) is a disease of calves characterised by haematopoietic depletion, mediated by ingestion of alloantibodies in colostrum. It has been linked epidemiologically to vaccination of the dams of affected calves with a particular vaccine (Pregsure) containing a novel adjuvant. Evidence suggests that BNP-alloantibodies are directed against MHC I molecules, induced by contaminant bovine cellular material from Madin-Darby Bovine Kidney (MDBK) cells used in the vaccine's production. We aimed to investigate the specificity of BNP-alloantibody for bovine MHC I alleles, particularly those expressed by MDBK cells, and whether depletion of particular cell types is due to differential MHC I expression levels. A complement-mediated cytotoxicity assay was used to assess functional serum alloantibody titres in BNP-dams, Pregsure-vaccinated dams with healthy calves, cows vaccinated with an alternative product and unvaccinated controls. Alloantibody specificity was investigated using transfected mouse lines expressing the individual MHC I alleles identified from MDBK cells and MHC I-defined bovine leukocyte lines. All BNP-dams and 50% of Pregsure-vaccinated cows were shown to have MDBK-MHC I specific alloantibodies, which cross-reacted to varying degrees with other MHC I genotypes. MHC I expression levels on different blood cell types, assessed by flow cytometry, were found to correlate with levels of alloantibody-mediated damage in vitro and in vivo . Alloantibody-killed bone marrow cells were shown to express higher levels of MHC I than undamaged cells. The results provide evidence that MHC I-specific alloantibodies play a dominant role in the pathogenesis of BNP. Haematopoietic depletion was shown to be dependent on the titre and specificity of alloantibody produced by individual cows and the density of surface MHC I expression by different cell types. Collectively, the results support the hypothesis that MHC I molecules originating from MDBK cells used in vaccine production, coupled with a powerful adjuvant, are responsible for the generation of pathogenic alloantibodies.